An Empirical Study on the Co-occurrence of Test Smells - Santana, Railana; Martins, Luana; Ribeiro, Márcio; Machado, Ivan (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2025: Anais do X Simpósio Brasileiro de Testes de Software Sistemático e AutomatizadoDO - 10.5753/sast.2025.14387, 2025)
The co-occurrence of test smells poses a challenge for refactoring test code, as these issues rarely appear in isolation. Consequently, developers often need to apply multiple transformations during refactoring, which increases complexity and effort. Therefore, it is essential to explore efficient strategies that reduce steps and practically allow the simultaneous refactoring of these problems. Although the literature already documents several test smells, the joint refactoring of these problems remains unaddressed. Therefore, this paper investigates the co-occurrence of test smells in test code (both at the class and test method level) and strategies to fix them efficiently, minimizing the number of transformations and preserving the behavior of the tests. To achieve this goal, we identified test smells using an automated tool in twenty-two open-source projects. We evaluated the co-occurrence between different types of test smells. Then, we ranked the thirty most frequent test smells pairs and suggested ways to refactor them in an integrated manner. Our findings can support developers in improving the quality of test cases, as our approach was designed with the industry’s reality in mind, where test smells often appear simultaneously.